First checklist of the herpetofauna (Amphibia, Reptilia) of the Kapas and Gemia Islands, Peninsular Malaysia, South China Sea - Muhamad F. Syafiq; Baizul Hafsyam Badli Sham; Mohamad Aqmal Naser; Muhammad Fahmi Ahmad; Quah, Evan Seng Huat; Larry L. Grismer; Amirrudin B. Ahmad (Pensoft Publishers, 2025)
Off the coast of Terengganu, Peninsular Malaysia, lie the Kapas and Gemia Islands. The biota, and particularly the herpetofauna, of these small, famous islands is poorly known. Opportunistic surveys were conducted on these islands during the dry and pre‑monsoon periods using visual encounter surveys (VES) as the method to record the herpetofauna. The surveys recorded five species of amphibians from four genera and three families, and 16 species of reptiles from 15 genera and 10 families. This report represents the first checklist of the herpetofauna of the Kapas and Gemia Islands, Terengganu, and it shows the unrealized biodiversity of small offshore islands in the archipelagos of the South China Sea. More extensive surveys should be conducted in the future to get a more complete understanding of the herpetofauna inhabiting these small islands, which face anthropogenic disturbances.